Analisa Sistem Informasi Akademik Menggunakan WebQual dan PIECES Frameworks Pada Universitas XYZ - Irdha Yunianto; Hindriyanto Dwi Purnomo; Sri Yulianto Joko Prasetyo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
This study aims to provide recommendations or policy suggestions in order to improve the quality of the academic information system (SIAKAD) for university operator or management. SIAKAD is a website-based application created to assist the process of managing data related to academics and has uses in managing campus or college management. Policy suggestions are compiled based on the analysis of higher education information system assessments with a comparison of the dimensions of WebQual and the PIECES Framework in measuring the quality of SIAKAD as a guide in improving or developing the quality for the better. The results of the analysis using the WebQual method with a value of 3.50 and the PIECES Framework with a value of 3.97 on the quality of the SIAKAD website produced the same results which were in the Good category with a score of 4 (3.43 - 4.23) based on the assessment criteria. The results of the recommendations in this study are expected to contribute to higher education management as a reference or decision support in improving the quality of the website-based academic information system (SIAKAD) for the better